2018
DOI: 10.1007/s13592-018-0589-8
|View full text |Cite
|
Sign up to set email alerts
|

The first detection of Nosema ceranae (Microsporidia) in the small hive beetle, Aethina tumida Murray (Coleoptera: Nitidulidae)

Abstract: In order to investigate the possible infection of Nosema ceranae in small hive beetle (SHB), Aethina tumida , in 2017, beetle specimens were sampled in Gainesville (Florida). By Real-Time PCR (qPCR), using previously developed primers based on the 16S rRNA gene, N. ceranae was detected in 7 out of 10 SHB specimens, proving that the microsporidia can be transmitted by the alien beetle. This is the first report of N. ceranae infection in A. tumida , although evaluated on a few specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…To date, only a few instances of individual SHBs bearing bee pathogens have been reported. This is the case for samples from Mexico (positive for L. passim , Apis mellifera filamentous virus (AmFV), C. bombi , Ascosphera apis , and Nosema ceranae [ 22 ]), Florida (positive for N. ceranae [ 20 ]), and other areas of the USA (positive for DWV, SBV and P. larvae [ 19 , 20 , 22 , 24 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few instances of individual SHBs bearing bee pathogens have been reported. This is the case for samples from Mexico (positive for L. passim , Apis mellifera filamentous virus (AmFV), C. bombi , Ascosphera apis , and Nosema ceranae [ 22 ]), Florida (positive for N. ceranae [ 20 ]), and other areas of the USA (positive for DWV, SBV and P. larvae [ 19 , 20 , 22 , 24 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Adult SHBs invade colonies, where they feed, thrive, and reproduce. This allows contact between SHBs and other bee pests and pathogens [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on ultra-structural and molecular investigations, a new Nosema species in Apis mellifera , namely N. neumanni (Chemurot et al 2017), was described in Uganda in 2017 [ 19 ]. The importance of N. ceranae spillover is not limited to the honey bee but also to other insect species like the bee-eater Merops apiaster [ 20 ], the South American native bumblebee, Bombus brasiliensis (Lepeletier, 1836) [ 21 , 22 ], stingless bees and social wasps [ 23 ], solitary bees [ 24 ], the small hive beetle, Aethina tumida (Murray, 1867) [ 25 ], etc. Numerous studies have indicated that N. ceranae has become a worldwide distributed microsporidian pathogen, including in Central Italy [ 26 , 27 ], Croatia [ 28 ], Lithuania [ 29 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides A. cerana and A. mellifera , the microsporidium was reported in several other hymenopteran species, and was also found in regurgitated pellets of bee-eaters [ 12 , 13 , 14 , 15 , 16 ]. It was also found in small hive beetles ( Aethina tumida) [ 17 ], although the possibility of transmission to hymenopterans remains unclear [ 18 ].…”
Section: Introductionmentioning
confidence: 99%